Kişiliğin korunması ve Veri Koruma Hukuku kapsamında unutulma hakkı - Turhan, Ayşe Melek (İstanbul Medipol Üniversitesi Sosyal Bilimler Enstitüsü, 2018)
İçinde bulunduğumuz internet çağında veri güvenliğinin tehlikeye girmesiyle yeni bir takım haklara ihtiyaç duyulmuştur. Kişilik hakkının etkin şekilde korunması için öncelikle kişisel verilerin korunması kavramı ortaya çıkmıştır. Ardından ise, kişisel veriler üzerindeki kontrolün veri sahibine verilmesi ve kişisel verilerin etkin şekilde korunabilmesi amacıyla unutulma hakkı ortaya çıkmıştır. Çalışmamızın birinci bölümünde, öncelikle unutulma hakkının tarihçesi ile unutulma hakkı kavramı, hakkın kapsamı ve sınırları ardından ise hakkın temelinde yatan kişilik hakkının korunması ele alınmıştır. Çalışmamızın ikinci bölümünde ise, unutulma hakkının korunmasını sağlayan kişisel verilerin korunması kavramı, Avrupa Birliği'ndeki kişisel verilerin korunmasına ilişkin düzenlemeler ve ülkemizde yürürlükte olan Kişisel Verilerin Korunması Kanunu ile birlikte incelenmiş; ardından ise, unutulma hakkının Avrupa Birliği Hukukunda korunması ve unutulma hakkına ilişkin Türk yargı kararları ele alınmıştır.

As the data security is imperiled in the new era of the internet age a set of rights was found to be needed to effectively protect personal data. In order to protect personality right effectively the concept of protection of personal data has emerged. Then ''Right to be Forgotten'' came into existence in order to give the full control of the personal data to the data owner and to protect the personal data of one efficiently. In the first part of the study, primarily, the history of the right to be forgotten and the right to be forgotten as a concept, have been discussed. Next, the scope and limits of the right have been examined and also personality right, which constitutes core of the right, itself has been explained. In the second part of our study, the concept of protection of personal data are highlighted, where the right to be forgotten is examined together with the regulations on the protection of personal data, in the European Union and the Law on the Protection of Personal Data in Turkey. Finally, the Turkish judicial decisions regarding the right to be forgotten and protection of the right to be forgotten in the European Union Law have been discussed.
Right to be forgotten under protection of personal rights and Data Protection Law
Keywords: Kişilik Hakkı; Kişisel Verilerin Korunması; Kişisel Veri; Unutulma Hakkı; Veri Koruma Hukuku; Data Protection Law; Personality Right; Personal Data Protection; Personal Data; Right to be Forgotten